Generative AI in English Language Teaching: Opportunities and Challenges - Saud, Dammar Singh (Journal of Jayaprithvi Multiple Campus, 2025)
The emergence of generative AI has significantly impacted English Language Teaching (ELT), presenting both opportunities and challenges. This study adopts a hermeneutic phenomenological approach to examine the experiences of four university-level English teacher educators who have incorporated generative AI into their teaching methodologies. By employing theoretical frameworks such as sociocultural theory and connectivism, the research explores how generative AI can tailor learning experiences, enhance language practice, and promote greater accessibility and inclusivity. The study also addresses issues related to the accuracy of AI outputs, ethical concerns, the need for teacher training, and the associated costs. Through semi-structured interviews and thematic analysis, the research offers comprehensive insights into the practical ramifications of AI in ELT. The results emphasize the importance of thoughtful integration, ongoing evaluation, adherence to ethical standards, and extensive professional development. This study contributes valuable perspectives to the discussion on AI in education and provides actionable insights for educators, policymakers, and developers.